Analisis Kualitas Butir Soal Ujian Sekolah Mata Pelajaran IPA Berdasarkan Dimensi Pengetahuan Faktual dan Konseptual Ditinjau Dari Konten dan Konteks - Yugo Rahmadhani; Irwan Koto Koto; Endang Widi Winarni (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2021)
This study aims to describe: (1) the proportion of cognitive levels; (2) the proportion of items on the dimensions of factual and conceptual knowledge in the basic competencies of grades IV, V, and VI; 3) the quality of the items based on the dimensions of factual knowledge in terms of content and context; and 4) the quality of the items based on the dimensions of conceptual knowledge in terms of content and context on the school exam questions for the subject of Natural Sciences for the 2018/2019 academic year. This type of research is a descriptive study with the method of documentation. The results obtained are: (1) The proportion of cognitive levels, including the level of knowing (C1) as many as 7 items (17.50%), understanding level (C2) as many as 20 items (50%), the level of implementing (C3) as many as 6 items (15%), and the level of analysis (C4) as many as 7 items (17.50%); (2) The proportion of items based on the dimensions of knowledge, including the dimensions of factual knowledge for class IV as many as 7 items (17.50%), class V with 4 items (10.00%), and class VI as many as 5 items (12, 50%). The dimensions of conceptual knowledge in class IV were 4 items (10.00%), class V had 10 items (25.00%), and class VI had 10 items (25.00%); (3) The results of expert validation based on the dimensions of factual knowledge in terms of content contained 7 items (17.50%) and context there were 9 items (22.50%); and (4) The results of expert validation based on the conceptual knowledge dimension in terms of content contained 9 items (22.50%) and context there were 15 items (37.50%).